Synthesis and key insights from the implementation of the gender sensitive Climate-Smart Agriculture monitoring framework in Central America: temporal and spatial dynamics in the Olopa (Guatemala) and Santa Rita (Honduras) Climate Smart Villages - Bonilla Findji, Osana; Eitzinger, Anton; Bejarano, Gustavo; Ortega, Angelly; Moreno, Manuel Francisco; Muriel, Juliana (2020)
Building on two years of implementation of the Climate-Smart Agriculture (CSA) monitoring framework in the Climate-Smart Villages of Olopa (Guatemala) and Santa Rita (Honduras), we i) synthetize gender disaggregated results and highlight key insights from the temporal and spatial dynamics observed in farmers’ socio-economic, climate and agricultural related conditions, ii) we examine the potential sociodemographic and socioeconomic variables influencing adoption of CSA practices to identify potential adoption typologies; and iii) assess the gender and age-disaggregated perceived effects of these practices on six outcome indicators: agricultural productivity and income, food access and diversity, climate vulnerability and labor time.